1990
DOI: 10.1002/macp.1990.021910120
|View full text |Cite
|
Sign up to set email alerts
|

Miscibility behavior in blends of poly(2,6‐dimethylphenylene oxide) and random or block copolymers of styrene with methyl methacrylate

Abstract: The miscibility in blends of poly(2,6-dimethylphenylene oxide) (PPO) with random or block copolymers of styrene and methyl methacrylate (MMA) was studied by light microscopy and glass transition temperature measurements. Blends of PPO and the random copolymers were found to be miscible up to a copolymer content of 18 wt.-% MMA. The transition from miscibility to immiscibility in these blends is independent of temperature in the range 100 to 350 "C. From these data, the segmental interaction parameter between u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It has been known that PPE is miscible with a-PS caused by strong attractive interactions (χ PPE/PS = −0.1) The question remains as to how PPE influences SEBS when there is an interfacial contact. Figure a shows a TEM micrograph of the SEBS / PPE interface after isothermal annealing for 15.25 h at 225 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been known that PPE is miscible with a-PS caused by strong attractive interactions (χ PPE/PS = −0.1) The question remains as to how PPE influences SEBS when there is an interfacial contact. Figure a shows a TEM micrograph of the SEBS / PPE interface after isothermal annealing for 15.25 h at 225 °C.…”
Section: Resultsmentioning
confidence: 99%
“…17 These favorable enthalpic interactions are also responsible for the miscibility of PPE with PS in block copolymers even in the case where PPE has a much larger molecular weight than the PS block. [18][19][20] The question remains as to how PPE influences SEBS when there is an interfacial contact.…”
Section: Sebs In Bulkmentioning
confidence: 99%
“…Karasz et al have been suggested that blends of poly(2,6‐dimethylphenylene oxide) (PPO) and random copolymers of styrene (S) and methyl methacrylate (MMA) were found to be miscible up to a copolymer content to 18 wt % of MMA. Above this critical MMA content, the blends of PPO/PSMMA exhibit two T g s occurring the phase separation 8. Some years ago, Paul and Barlow have enumerated several cases of miscible binary blends involving copolymers when their corresponding homopolymers are not similarly miscible 7.…”
Section: Introductionmentioning
confidence: 99%